Lightweight PUF-based anonymous authentication protocol in V2G - FAN Xinyue; LIU Jie; HE Jiahui (Tongxin xuebao)
To address the issues of incomplete functionality, high communication overhead, and high computational cost in existing vehicle-to-grid (V2G) network authentication protocols, a lightweight anonymous authentication protocol based on physical unclonable function (PUF) was proposed, which could resist machine learning modeling attacks. The proposed protocol employed Hash functions and the ASCON cryptographic algorithm to achieve rapid three-party authentication and key negotiation among vehicles, charging stations, and energy providers. By combining fuzzy extractors with biometric features and user passwords, two-factor authentication, password and biometric feature update functions were implemented. Additionally, an effective user revocation strategy was provided through a cryptographic dynamic accumulator. The ROR model and Scyther formal validation tool proved the security of the proposed protocol, and the informal security analysis showed that the proposed protocol was resistant to a variety of security attacks, such as physical attacks, location forgery attacks and privileged insider attacks. The performance comparison analysis with the protocols of recent years shows that the proposed protocol reduces the communication overhead by about 35.9% and the computational cost by 29.9% on average, which is highly suitable for resource-limited V2G environments.